Heterogeneity of symptoms and functions among women receiving chemotherapy for breast cancer in China: A multicentre, cross-sectional study - Cai, Tingting; Zhou, Tingting; Yuan, Changrong; Yu, Chunfang; Ni, Feixia; Sheng, Zhiren (Frontiers in Public Health, 2022)
Background: Currently, few studies have explored the heterogeneity of symptoms and functions in patients with breast cancer. This study aimed to identify the subgroups of symptoms and functions in women receiving chemotherapy for breast cancer and determine whether the subgroups differed in demographic and clinical characteristics. Methods: A cross-sectional multicenter survey involving five hospitals in Zhejiang, Shanghai, Shandong, and Guangxi provinces of Mainland China was implemented between August 2020 to December 2021. Participants completed questionnaires that included the PROMIS-57, PROMIS cognitive function short form, and demographic and clinical characteristics. Latent class analysis was performed, followed by chi-square test and analysis of variance. Subsequently, significant variables were included in multinomial logistic regression. Results: A total of 1,180 patients were investigated, with an average age of 48.9 years. Three classes were identified: low symptom burdens and functions group (26.2%, Class 1), moderate symptom burdens and functions group (16.9%, Class 2), and low symptom burdens and high functions group (56.9%, Class 3). Compared with patients in Class 1 and 3, those in Class 2 consistently showed a higher tendency of having urban employee health insurance (odds ratio=2.506, P < 0.05) and rural health insurance (odds ratio=2.207, P < 0.05). Additionally, patients in Class 2 tended to be in their fourth cycle of chemotherapy. However, receiving chemotherapy and surgery increased the likelihood of belonging to Class 1. Conclusions: A high proportion of patients experienced varying degrees of these issues, suggesting that attention is warranted for women with breast cancer undergoing chemotherapy. Patients with the urban employee basic medical system, the new rural cooperative medical system and in the early stage of chemotherapy cycles were more likely to have symptom burdens. Middle-aged postmenopausal women reported varying degrees of cognitive issues. Additionally, surgery increased the presence of potential long-term effects in functional levels.